2006
DOI: 10.1103/physrevb.73.134202
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the embedding environment on the strain within small rings in siliceous materials

Abstract: The effect of the local environment on the energetic strain within small ͑SiO͒ N rings ͑with N =2,3͒ in silica materials is investigated via periodic model systems employing density functional calculations. Through comparison of the energies of various nonterminated systems containing small rings in strained and relatively unstrained environments, with alpha quartz, we demonstrate how small ring strain is affected by the nature of the embedding environment. We compare our findings with numerous previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
4
23
1
Order By: Relevance
“…All NPs in this low hydroxylation sub-set, as for the full set of all (SiO 2 ) 16 (H 2 O) N isomers considered, do not exhibit terminal oxygen defects. However, at this low degree of hydroxylation, many NPs possess rather strained threemembered (SiO) 3 rings 47 indicating that further ring-opening via hydroxylation would be energetically favourable. 41 The N = 8 sub-set of NPs can be regarded as having a high 50% degree of hydroxylation and often exhibit between one and three geminal silanol groups (i.e., two hydroxyls bound to one silicon atom).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All NPs in this low hydroxylation sub-set, as for the full set of all (SiO 2 ) 16 (H 2 O) N isomers considered, do not exhibit terminal oxygen defects. However, at this low degree of hydroxylation, many NPs possess rather strained threemembered (SiO) 3 rings 47 indicating that further ring-opening via hydroxylation would be energetically favourable. 41 The N = 8 sub-set of NPs can be regarded as having a high 50% degree of hydroxylation and often exhibit between one and three geminal silanol groups (i.e., two hydroxyls bound to one silicon atom).…”
Section: Methodsmentioning
confidence: 99%
“…In silica, the O-Si-O angle is largely constrained by the rigid tetrahedrality of the SiO 4 sub-units. In pure silica, these tetrahedra can be distorted by highly strained small (SiO) n rings 47,49 or terminating defects 50,51 typically found in anhydrous silica. As low barrier reactions with water are generally favoured at such sites, quickly leading to ring opening or healing of terminating defects, [52][53][54][55][56] it is expected that the O-Si-O angle distribution in nanosilica should be relatively narrow and invariant above a certain degree of hydroxylation.…”
Section: O-si-o Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that the exclusively silanone-terminated clusters ͑A, B, F͒ show an interesting trend between ͑SiO͒ n n-membered-ring strain and absorption onset. Previous work 68 has demonstrated that the ring size and the associated strain energy in silica decreases strongly in the order twomembered ringϾ three-membered ringϾ four-membered ring, where the latter is found to be almost ring-strain free. When moving from an inherently highly strained system ͑cluster A, where the silicon centre of the silanone group is part of a two-membered ring͒ to lesser ͑cluster B with the silicon of the silanone groups forming part of either a two or three-membered ring͒ and an even lesser strained systems ͑cluster F where the silicon of the silanone groups forms part of a four-membered ring͒ the absorption onset consistently lowers.…”
Section: Resultsmentioning
confidence: 91%
“…Generally, structures made mainly with rings containing more than three -(Si-O)-units are found to have low tetrahedral distortion. [39] Interestingly, several of the structures shown in Fig. 3, can be viewed as being generated from condensation of building blocks of smaller sized isomers.…”
Section: Resultsmentioning
confidence: 99%